PELAYANAN PERIZINAN BIDANG KEHUTANAN PADA KANTOR DINAS KEHUTANAN DI KABUPATEN KUTAI TIMUR - Dedy Wahyudi (Jurnal Paradigma (JP), 2017)
The purpose of this study is to describe and analyze the Licensing Services Division of  Forestry Agency in East Kutai District Forestry Office. The research findings show that forestry licensing service held East Kutai Regency Forest Service is implementable optimally. In order to meet the expectations of public service users, the agency has implemented an integrated service pattern. Because of this reason, it gain big appreciation among entrepreneurs engaged in the rehabilitation of forests and land use, because it is no longer confronted by lines convoluted bureaucracy and all licensing matters can be resolved more effectively.